2015
DOI: 10.1186/s12903-015-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Albanian version of the Orofacial Esthetic Scale: OES-ALB

Abstract: The aim was to adapt the Orofacial Esthetic Scale (OES) and to test psychometric properties of the Albanian language version in the cultural environment of the Republic of Kosovo.MethodsThe OES questionnaire was translated from the original English version according to the accepted techniques. The reliability (internal consistency), and validity (construct, convergent and discriminative) were tested in 169 subjects, test-retest in 61 dental students (DS), and responsiveness in 51 prosthodontic patients with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 34 publications
(31 reference statements)
7
37
1
Order By: Relevance
“…The OES has one total score (Larsson et al, 2010). The instrument has already been translated and adapted for different countries (Alhajj et al, 2017;Bimbashi et al, 2015;N'Guyen-Van, Moreau & Braud, 2019;Persic et al, 2011;Reissmann et al, 2015;Simancas-Pallares et al, 2018;Wetselaar et al, 2015;Zhao & He, 2013) and applied to different contexts, such as the general population (John et al, 2012), specific dental patients such as denture wearers (Larsson et al, 2010), and dental patients in general (Reissmann et al, 2019). In addition, some studies have evaluated the psychometric properties of OES, attesting to its validity and reliability for the Swedish general population (John et al, 2012) and for the population of North American dental patients (Reissmann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The OES has one total score (Larsson et al, 2010). The instrument has already been translated and adapted for different countries (Alhajj et al, 2017;Bimbashi et al, 2015;N'Guyen-Van, Moreau & Braud, 2019;Persic et al, 2011;Reissmann et al, 2015;Simancas-Pallares et al, 2018;Wetselaar et al, 2015;Zhao & He, 2013) and applied to different contexts, such as the general population (John et al, 2012), specific dental patients such as denture wearers (Larsson et al, 2010), and dental patients in general (Reissmann et al, 2019). In addition, some studies have evaluated the psychometric properties of OES, attesting to its validity and reliability for the Swedish general population (John et al, 2012) and for the population of North American dental patients (Reissmann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, this should not be a limitation. Other studies already proved convergent validity with external ratings of Oro‐facial Appearance, known‐groups validity, responsiveness and test‐retest reliability of the OES . We see no reason why this should be related to the method of administration.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, the Oro‐facial Esthetic Scale (OES), an 8‐item instrument, was developed to overcome this drawback and to comprehensively assess Oro‐facial Appearance from the patient perspective . The OES is unidimensional, exhibited good psychometric properties and is available in several languages . Furthermore, norm values were provided for the general population …”
Section: Introductionmentioning
confidence: 99%
“…The OES instead evaluates the overall satisfaction of the patient with his/her esthetic appearance. As the most common instrument used in research, the OES has good psychometric properties and has been adapted cross-culturally to several languages such as; Croatia,Chinese,Albanian,Dutch,Germany,Arabic,and Spanish [25,29,[32][33][34]37,40,41]. Although the instrument developed by Tortopidis et al showed good reliability, there has been no report of its use in other published studies.…”
Section: Discussionmentioning
confidence: 99%